2009
DOI: 10.1007/s11144-009-0099-9
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxy- and alkoxycarbonylation of aryl iodides catalyzed by polymer-supported palladium

Abstract: The efficient carbonylation of aryl iodides catalyzed by palladium immobilized on polymers in water or methanol under very mild conditions is reported. The catalyst can be recycled several times without loss of activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Previously, we developed a catalytic system of PdNPs supported on a soluble statistical copolymer of N ‐vinylimidazole with N ‐vinylcaprolacam (30 %; PVI‐PVCL), which revealed high activity and recyclability in the Heck reaction,12 the cyanation of aryl halides,13 and the carbonylation of aryl iodides 14. Polymer PVI‐PVCL successfully models natural enzymes on the basis of peptide macromolecules 15.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we developed a catalytic system of PdNPs supported on a soluble statistical copolymer of N ‐vinylimidazole with N ‐vinylcaprolacam (30 %; PVI‐PVCL), which revealed high activity and recyclability in the Heck reaction,12 the cyanation of aryl halides,13 and the carbonylation of aryl iodides 14. Polymer PVI‐PVCL successfully models natural enzymes on the basis of peptide macromolecules 15.…”
Section: Resultsmentioning
confidence: 99%
“…Beletskaya and Ganina reported palladium nanoparticles immobilised on poly(N-vinylimidazole-co-N-vinylcaprolactam) (PdNPs/PVI-PVC) in methanol for the alkoxycarbonylation of aryl iodides (Scheme 40). 42 The PdNPs/PVI-PVC catalyst could be recycled several times without loss of activity.…”
Section: Heterogeneous Palladium Catalysed Alkoxycarbonylation Reacti...mentioning
confidence: 99%
“…Use of the Pd-PS-PEO catalyst in hydroxycarbonylation reactions gave excellent results. The hydroxycarbonylation of meta - and para -iodobenzoic acids was carried out in water at room temperature using PdNPs micellar catalyst and KOH as a base [ 23 ]. Both reactions proceeded with full conversion to give quantitative yields of phthalic acids after 24 h. For 3-iodobenzoic acid, the catalyst was recycled 11 times, with full isolation of the product in the first five cycles and spectroscopic determination of yields in the final six cycles ( Figure 7 ).…”
Section: Palladium Nanoparticlesmentioning
confidence: 99%
“…The efficient hydroxycarbonylation of aryl iodides catalyzed by Pd-PS-PEO-CPC prompted us to carry out alkoxycarbonylation in methanol using PdCl 2 -PVI-PVC as a pre-catalyst [ 23 ]. The study of reaction conditions has shown that the best result can be obtained with 1 mol% Pd/5 mol% PVI-PVC at 55 ºC and 1 atm CO using Et 3 N as a base ( Table 3 , entry 12).…”
Section: Palladium Nanoparticlesmentioning
confidence: 99%